Educational Quality Management at Inpres Kema III Primary School - Tangkudung, Ernny Ningsy (International Journal Labs, 2023)
This research aims to analyze and describe: the quality planning process, quality implementation, and quality evaluation at SD INpres Kema III, North Minahasa Regency. This research uses a naturalistic qualitative method, where data collection uses techniques: participant observation, interviews, and documentation studies. Based on the results of data analysis, it was concluded that 1) the process of improving the quality at SD Inpres Kema III went through stages: first, evaluation and analysis of the implementation of learning in the previous academic year by the principal, second, preparation of a quality improvement plan based on the results of the evaluation of the implementation of learning in the previous year, third, presentation of the evaluation results in the principal and the new quality improvement program plan at the meeting at the beginning of the school year (attended by the teacher council and school committee), the fourth discussion of the work program plan for the new school year, 2) quality implementation is by the quality improvement plan. In the process, the school principal acts as a